Drivers of increasing energy consumption in Europe and policy implications. (February 2020) - Thomas, Samuel; Rosenow, Jan
Abstract: Two years ago, the EU appeared to be well on the way to meeting its 2020 energy efficiency targets. 2014 final energy consumption was lower than in any year since the 1980s and lower than the level required in 2020. Since then, energy consumption has risen in two consecutive years and looks set to have kept on increasing. If these short-term trends continue, the 2020 targets will be missed. In this context, this paper analyses the drivers of recent increases in energy consumption, using index decomposition analysis breaking down changes in an aggregate indicator and assigning the effects to a number of predefined factors. We rely on a decomposition approach that is widely used across Europe and has been developed over more than 20 years as part of the Odyssee-Mure project. The paper also draws upon discussions at an expert workshop organised by the European Commission. The paper does identify areas where energy efficiency policies could be strengthened. We suggest that more ambitious policies are needed to drive improvements in building fabric and space heating efficiency, and that a greater focus on measurement, verification and enforcement of policies would improve the effectiveness of existing policies. Highlights: Analysis of drivers of recent increases in EU energy consumption using decomposition analysis. Identified economic growth as leading to increase in energy consumption. Decomposition analysis suggests that energy efficiency progress has slowed. More ambitious policies are needed in building fabric and space heating efficiency. A greater focus on measurement, verification and enforcement is required.